Mechanical Wear Characteristics of 170 kV Gas-Insulated Switchgear Circuit-Breaker Contacts Before Arc Initiation: An Accelerated Lifetime Test Approach - Jong-Geon Lee; Jae-Hong Koo (IEEE Access)
This study investigates the mechanical wear characteristics of 170 kV gas-insulated switchgear (GIS) circuit breaker contacts by conducting accelerated life testing. Samples identical to those used in 170 kV GIS were subjected to up to 20,000 cycles, which is the maximum guaranteed lifespan. Visual inspections, contact resistance measurements, mass change assessments, and operational characteristic evaluations, including trip and close coil excitation currents, were performed. Considerable surface damage and increased contact resistance were observed after approximately 12,000 operations, indicating that mechanical wear before arc formation had a substantial impact on the electrical performance and lifespan of circuit breaker contacts. The results reveal that the lifetime and reliability of GIS circuit breakers can be improved by addressing the pure mechanical wear before arc occurrence during the maintenance of GIS circuit breakers.